الحماية القانونية للملكية الصناعية في التشريع الجزائري - رجب, سارة (جامعة الوادي -University eloued, 2017)
إن تطور الدولة يتوقف إلى حد كبير على درجة إبداع مواطنيها من ذوي العقول المفكرة في مجال الابتكار والإبداع، كما أن تقدم أي مجتمع يتوقف على مدى تشجيع أصحاب الإيداع الفكري وتهيئة الوسائل القانونية والمادية على التي تكفل لهم الطمأنينة والاستغلال في عملهم، وهو الأمر الذي رهنه الدول الصناعية بتعجيلها حماية حقوق ملكية الصناعية وطنياً هو الأكثر فعالية واتصالاً بالنمو الاقتصادي، حيث تخطى حقوق الملكية الصناعية برعاية وطنية ودولية نظراً للأهمية التي تكتسبها، إلا أننا سنتطرق إلى الحماية الوطنية في دراستنا هذه تتفرع إلى قسمين رئيسين: الحقوق الواردة على الابتكارات الصناعية الجديدة هو الفرع الذي يتعلق بالابتكارات من حيث موضوع المنتوجات، أي التي لها طابعاً نفعياً وأهمها هي براءة الاختراع وقد يتعلق ابتكار جديد من حيث شكل المنتوجات أي ابتكارات ذات الطابع الفني وهي الرسوم والنماذج الصناعية، وقد تكون تلك التي تجمع بين الابتكار النفعي والشكل الفني وهي التصميمات الشكلية للدوائر المتكاملة The development of the state depends to a large extent on the creativity of its citizens with creative minds in the field of innovation and creativity, and the progress of any society depends on the extent of encouraging intellectual depositors and the creation of legal and material means to ensure their tranquility and exploitation in their work, Industrial rights are the most effective and linked to economic growth, as it exceeded the industrial property rights under national and international patronage because of the importance it acquires. However, we will address the national protection in our study, which is divided into two main parts: The rights contained in the new industrial innovations are those which relate to innovations in terms of the subject matter of the products, that is, which have a beneficial nature. The most important is the patent. A new innovation in terms of the form of products may be any innovations of a technical nature, industrial designs, Nafei and technical form, which are the formal designs of integrated circuits.
ماستر اعمال
Keywords: الملكية الصناعية – براءت الأختراع- الرسوم والنماذج الأخترعية.; Industrial Property - Patents - Creative Designs.